Implementation of E-Government through the Sidoarjo Regency Electronic Office Manuscript Application (E-Buddy) (Case Study in Kajeksan Village Government, Tulangan District, Sidoarjo Regency) - Khofifatul Ummah; Ilmi Usrotin Choiriyah (Budapest International Research and Critics University, 2023)
The purpose of this study was to find out and analyze the implementation of e-government through the application of the Sidoarjo Regency electronic official document (E-Buddy) in the Kajeksan Village Government, Tulangan District, and Sidoarjo Regency. The background of this research is the declining disposition of official letters in the E-Buddy application at the Kajeksan Village Government from 2021 to October 2022. This research method uses a qualitative approach with a descriptive research type. The results of the study show that first, the communication indicators have not been carried out optimally, namely in terms of outreach and technical guidance regarding the implementation of the E-Ebuddy application. Second, an indicator of human resources, namely the ability of some village officials as implementers have not fully adapted to the E-Buddy application. The three indicators of disposition or attitude of several Kajeksan Village Government officials are still not consistent and responsive in processing letters, especially in the disposition of letters through the E-Buddy application so that the utilization of the application has not been utilized optimally. The four indicators of bureaucratic structure, the Kajeksan Village Government have not provided implementing instructions or a special procedural mechanism in implementing the E-Buddy application. Especially in the disposition of letters through the E-Buddy application so that the utilization of the application has not been utilized optimally. The four indicators of bureaucratic structure, the Kajeksan Village Government have not provided implementing instructions or a special procedural mechanism in implementing the E-Buddy application. Especially in the disposition of letters through the E-Buddy application so that the utilization of the application has not been utilized optimally. The four indicators of bureaucratic structure, the Kajeksan Village Government have not provided implementing instructions or a special procedural mechanism in implementing the E-Buddy application.